(untitled) (Indian Journal of Chemistry (IJC), 2025)
This article has been retracted at the request of the Authors. Reason: The article bears substantial resemblance with the paper that has already appeared in Chemistry Research Journal, Vol. 5, Number 4, pp. 201-210 (2020) by Mohamed I Hegab, Hala E. M. Tolan, Eman M H. Morsy, Abdelsalam I. S., Alaa M. Saleh, Farouk A. Gad and, Farouk M. E. Abdel-Megeid.